GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 339 species occurrences available in GBIF matching the query: TaxonKey: Selaginella umbrosa Lem. ex Hieron.. The dataset includes 339 records from 34 constituent datasets: 11 records from Phanerogamic Botanical Collections (S). 20 records from Naturalis Biodiversity Center (NL) - Botany. 1 records from SPF - Herbário da Universidade de São Paulo. 1 records from UFP - Herbário UFP - Geraldo Mariz. 5 records from Plantae of Costa Rica (INBio). 2 records from MBM - Herbário do Museu Botânico Municipal. 1 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 7 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 2 records from Australia's Virtual Herbarium. 3 records from CONN. 12 records from NMNH occurrence DwC-A. 1 records from OAC-BIO Herbarium. 1 records from Jardin botanique de Montréal (JBM). 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 123 records from Tropicos Specimen Data. 33 records from Natural History Museum (London) Collection Specimens. 1 records from Andes to Amazon Biodiversity Program. 1 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Herbario de la Universidad de Sevilla, SEV-Historico. 33 records from herbario. 1 records from NSW herbarium collection. 1 records from USF Herbarium. 1 records from Field Museum of Natural History (Botany) Seed Plant Collection. 28 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from SBT-Living. 8 records from Bernice P. Bishop Museum. 4 records from Royal Botanic Garden Edinburgh Herbarium (E). 7 records from Instituto de Ciencias Naturales. 5 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 2 records from Instituto de ciencias naturales. 1 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 13 records from SysTax - Botanical Gardens. 4 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 1 records from Herbarium WRSL, Main Collection.
Keywords: GBIF; biodiversity; species occurrences